2016
DOI: 10.1017/s1368980016000641
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns extracted from the current Japanese diet and their associations with sodium and potassium intakes estimated by repeated 24 h urine collection

Abstract: Objective: To identify dietary patterns in the current Japanese diet and evaluate the associations between these patterns and Na and K intakes. Design: Dietary patterns were extracted by factor analysis from the intakes of food groups assessed with a validated self-administrated diet history questionnaire. Na and K intakes and urinary Na:K were assessed by repeated 24 h urine collection. Subjects: Healthy Japanese adults aged 20-69 years (353 men and 349 women). Setting: Twenty study areas in twenty-three pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
3
16
1
Order By: Relevance
“…Mediterranean dietary pattern and DASH are two ways of eating to protect from hypertension and non-communicable diseases including CVD, type 2 diabetes, stroke and obesity, may improve health status and reduce total lifetime costs (23)(24)(25)(26). Our present results were in line with those of previous studies that investigated the association between Japanese dietary patterns and urinary Na and K concentration, in which the patterns with high loadings for fish and vegetables were positively associated with high urinary K concentration (10). Furthermore results of the current study provide more evidence on previous studies reporting significant inverse association between "nuts, seeds, fruits and fish" dietary pattern and urinary Na/K ratio (11).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mediterranean dietary pattern and DASH are two ways of eating to protect from hypertension and non-communicable diseases including CVD, type 2 diabetes, stroke and obesity, may improve health status and reduce total lifetime costs (23)(24)(25)(26). Our present results were in line with those of previous studies that investigated the association between Japanese dietary patterns and urinary Na and K concentration, in which the patterns with high loadings for fish and vegetables were positively associated with high urinary K concentration (10). Furthermore results of the current study provide more evidence on previous studies reporting significant inverse association between "nuts, seeds, fruits and fish" dietary pattern and urinary Na/K ratio (11).…”
Section: Discussionsupporting
confidence: 91%
“…In our population, Western dietary pattern was associated with higher Na/K and traditional dietary pattern was associated with lower Na/K ratio. Similarly, Noodle pattern (10), and "snacks, fast food, soft drinks" pattern (12) were positively associated with urinary Na concentration in previous studies.…”
Section: Discussionsupporting
confidence: 53%
“…The “plant food and fish” dietary pattern revealed in the present study had certain characteristics consistent with the former, whereas the “animal food and oil” dietary pattern had certain characteristics in common with the latter. Further to these two patterns, previous Japanese studies similarly identified a third pattern (i.e., the “bread and dairy” pattern) [ 21 , 22 , 23 , 24 , 25 ], which may be considered neither healthy nor unhealthy owing to an extremely low intake of whole grain foods (including bread) in Japan [ 41 , 42 ] and potential health benefits of dairy products [ 43 ]. The present study, based on data from national dietary surveys, thus confirms these major patterns in the Japanese diet.…”
Section: Discussionmentioning
confidence: 99%
“…Recent Japanese diets typically include high intakes of refined grains (mainly white rice), seaweeds, vegetables, fish, soybean products, and green tea, as well as low intakes of whole grains, processed meat, nuts, and soft drinks [ 19 , 20 ]. While a number of Japanese studies have utilized PCA to determine dietary patterns [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], recent secular trends in dietary patterns remain unknown. Data from food balance sheets from 1960 to 2005 suggest that the Japanese diet has been undergoing Westernization: during this period, the per-capita supply of meat/poultry and fats/oils markedly increased, the rice supply sharply decreased, and the supply of vegetables, fruits, and fish/shellfish remained relatively stable [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, higher salt intake was observed in the highest jMD category. It is attributable to habitual consumption of higher salt Japanese foods, such as dried fish, canned tuna, and fish paste products (34). In a recent epidemiologic study (35), it is also reported that Japanese adults with higher urinary sodium excretion consumed a significantly greater amount of salty Japanese foods, such as salted fish, miso soup, and Japanese pickles.…”
Section: Discussionmentioning
confidence: 99%